Effectiveness of continuous glucose monitoring in pregnant women with diabetes: randomised clinical trial. (25th September 2008) - Murphy, Helen R; Rayman, Gerry; Lewis, Karen; Kelly, Susan; Johal, Balroop; Duffield, Katherine; Fowler, Duncan; Campbell, Peter J; Temple, Rosemary C
Abstract : Objective To evaluate the effectiveness of continuous glucose monitoring during pregnancy on maternal glycaemic control, infant birth weight, and risk of macrosomia in women with type 1 and type 2 diabetes. Design Prospective, open label randomised controlled trial. Setting Two secondary care multidisciplinary obstetric clinics for diabetes in the United Kingdom. Participants 71 women with type 1 diabetes (n=46) or type 2 diabetes (n=25) allocated to antenatal care plus continuous glucose monitoring (n=38) or to standard antenatal care (n=33). Intervention Continuous glucose monitoring was used as an educational tool to inform shared decision making and future therapeutic changes at intervals of 4-6 weeks during pregnancy. All other aspects of antenatal care were equal between the groups. Main outcome measures The primary outcome was maternal glycaemic control during the second and third trimesters from measurements of HbA1c levels every four weeks. Secondary outcomes were birth weight and risk of macrosomia using birthweight standard deviation scores and customised birthweight centiles. Statistical analyses were done on an intention to treat basis. Results Women randomised to continuous glucose monitoring had lower mean HbA1c levels from 32 to 36 weeks' gestation compared with women randomised to standard antenatal care: 5.8% (SD 0.6) v 6.4% (SD 0.7). Compared with infants of mothers in the control arm those of mothers in the intervention arm had decreased mean birthweight standard deviation scores (0.9 v 1.6; effect size 0.7 SD, 95% confidence interval 0.0 to 1.3), decreased median customised birthweight centiles (69% v 93%), and a reduced risk of macrosomia (odds ratio 0.36, 95% confidence interval 0.13 to 0.98). Conclusion Continuous glucose monitoring during pregnancy is associated with improved glycaemic control in the third trimester, lower birth weight, and reduced risk of macrosomia. Trial registration Current Controlled Trials ISRCTN84461581 .